2017
DOI: 10.1139/cjps-2017-0228
|View full text |Cite
|
Sign up to set email alerts
|

Annual and Perennial Forages for Fall/Winter Grazing

Abstract: Extending the grazing season by maintaining beef cattle on pasture in the fall/winter has been adopted by many producers on the Prairies as it reduces the need for mechanical harvesting and can lower labour and manure management costs relative to feeding cattle in confinement. Annual and perennial forages, alone or in combination, offer the potential for low-input grazing while maintaining animal productivity. Using a range of data sources, this paper will review the methods available for extending the grazing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…With swath grazing, the effort required for livestock to access winter forage is reduced, allowing livestock access to biomass and grain, even in deep snow. There have been numerous advances in swath grazing with the development of forage cultivars suited for frigid climates (McGeough et al, 2017). Autumn interseeding techniques have enabled small grains to be seeded and grazed following fall harvest of the primary crop (AAFC, 2017; McLelland and Brook, 2018).…”
Section: Impacts Of Integrated Crop–livestock Systems On Crop Productmentioning
confidence: 99%
“…With swath grazing, the effort required for livestock to access winter forage is reduced, allowing livestock access to biomass and grain, even in deep snow. There have been numerous advances in swath grazing with the development of forage cultivars suited for frigid climates (McGeough et al, 2017). Autumn interseeding techniques have enabled small grains to be seeded and grazed following fall harvest of the primary crop (AAFC, 2017; McLelland and Brook, 2018).…”
Section: Impacts Of Integrated Crop–livestock Systems On Crop Productmentioning
confidence: 99%
“…Meints et al (2001) found that post-harvest residue management was impacted Seed yield potential is also impacted by fertility (Wang et al 2013), genetics (e.g. Meints et al 2001;Cattani 2017) and adaptation to the growth environment (e.g. Cattani et al 2004;Zhang et al 2017).…”
Section: Overview Of Forage Seed and Perennial Grain Agronomy Researchmentioning
confidence: 99%
“…Table 5 shows a forage quality comparison of stockpiled intermediate wheatgrass between two renovation treatments. The first treatment was clipping to 5 cm and 60 kg ha Other issues that may become important will include the potential for reduced perenniality as harvest index increases (Zhang and Jiang 2000;Smaje 2015;González-Paleo et al 2016), the continuity of productivity (Cattani 2017) and pest infestations as area planted increases.…”
Section: Perennial Grain Agronomymentioning
confidence: 99%
“…Biligetu et al [34] showed that ALF with WWG or RWR had higher CP level, consistent with the current study. In contrast, McGeough et al [56] stated that CWG, MBG, WWG, northern wheatgrass, and green needlegrass in mixture with ALF showed low protein levels ranging from 5.0 to 10.7%, suggesting advanced plant maturity. All binary mixtures at both sites had similar TDN concentration, meeting beef cow nutrient requirements (440.9 to 640.5 g kg −1 ) [54].…”
Section: Forage Nutritive Valuementioning
confidence: 93%